Religion, Trust, and Vaccine Hesitancy in Australia: An Examination of Two Surveys - Aechtner, Thomas (Journal for the academic study of religion, 2022)
Religion has been identified as a potential driver of vaccine hesitancy. Nevertheless, the connections between religion and immunisation refusal can be complex, while there is a deficit of research exploring religion and vaccination doubts in Australia. With that in mind, this study considers Australian vaccine hesitancy with respect to religion and trust by analysing the 2018 Australian Survey of Social Attitudes and the Australian dataset of the 2018 Wellcome Global Monitor. Statistical analyses reveal no significant correlations between religion and vaccine hesitancy, while participants with negative vaccine attitudes identify that they do not have religious reasons for being vaccine hesitant. Nonetheless, a higher proportion of respondents with negative vaccine attitudes self-identify as religious or spiritual and maintain pro-religious views. It was also found that negative vaccine attitudes are correlated with unfavourable perceptions of both Jews and Muslims. Notably, religious self-identification divides two main groups of vaccine hesitant participants, described as Religious Conservatives and Nonreligious Progressives. These groups diverge on sexual ethics and social concerns, as well as around whether they trust in science as opposed to religion, while differing in their perceptions of Jews. What unites these vaccine hesitant participants, however, is a mutual lack of trust in government and scientists.